Efficacy of ear lavage with 3% hydrogen peroxide solution (oxydol) for refractory aural discharge related to acute infantile otitis media - Uno Yoshifumi (Otology Japan, 2006)
We investigated the efficacy of ear lavage with 3% hydrogen peroxide solution (oxydol) for refractory aural discharge related to acute otitis media after tympanotomy or insertion of a ventilation tube. The subjects were 30 patients (55 ears) in whom aural discharge persisted for 10 days or more despite therapy with antimicrobial agents. Ear lavage with 3% hydrogen peroxide solution (oxydol) was initiated, and antimicrobial agents was discontinued. Ear lavage was continued every day until aural discharge disappeared. In all patients, the disappearance of aural discharge was achieved within 14 days (mean: 6.9 days). In particular, the interval until its disappearance was 12 to 14 days (mean: 13.0 days) in patients with acute MRSA-related otitis media, but 7 days or less (mean: 6.0 days) in those in whom other types of bacteria were detected.Thus, ear lavage with 3% hydrogen peroxide solution (oxydol) was effective for refractory aural discharge related to acute otitis media after tympanotomy or insertion of a ventilation tube for the following reasons:1) 3% hydrogen peroxide solution (oxydol) destroyed the lipid membrane, DNA, and cellular contents of bacteria by generating hydroxy radicals.2) Oxygenation of the middle ear cavity via decomposition of 3% hydrogen peroxide solution (oxydol) normalized middle ear mucosa.3) Oxygenation of the middle ear cavity influenced the morphology of the pneumococcal membrane; it changed from the strongly pathogenic opaque type to the less pathogenic transparent type.